2013
DOI: 10.1155/2013/235056
|View full text |Cite
|
Sign up to set email alerts
|

eNOS Gene Variants and the Risk of Premature Myocardial Infarction

Abstract: BACKGROUND: Endothelial nitric oxide synthase (eNOS) as well as nitric oxide play an important role in the regulation of cardiovascular function. There are limited and controversial data regarding the impact of polymorphisms of eNOS gene that is implicated in the vasoconstrictive properties of the endothelium in the pathogenesis of premature myocardial infarction (MI).OBJECTIVE: We examined whether two common polymorphisms of eNOS gene (G894T and T786C) are associated with the development of premature MI.METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Among subgroups for Glu298Asp, 17 studies belonged to the European, [2] , [3] , [5] , [15] , [18] , [20] , [21] , [28] , [32] , [37] [39] , [53] [65] 14 to the Middle Eastern, [14] , [16] , [23] , [66] – [76] 10 to the Asian, [10] , [11] , [22] , [77] – [83] 8 to the Asian-Indian [13] , [84] – [90] and 1 to the African [57] group. ( Tables 1 and 2 ) The Asian-Indian subgroup in all its genetic models showed low heterogeneity ( I 2 range = 18–23% and P Q range = 0.26–0.28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among subgroups for Glu298Asp, 17 studies belonged to the European, [2] , [3] , [5] , [15] , [18] , [20] , [21] , [28] , [32] , [37] [39] , [53] [65] 14 to the Middle Eastern, [14] , [16] , [23] , [66] – [76] 10 to the Asian, [10] , [11] , [22] , [77] – [83] 8 to the Asian-Indian [13] , [84] – [90] and 1 to the African [57] group. ( Tables 1 and 2 ) The Asian-Indian subgroup in all its genetic models showed low heterogeneity ( I 2 range = 18–23% and P Q range = 0.26–0.28).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty nine case-control studies [5] , [17] , [22] , [23] , [27] , [28] , [31] , [32] , [37] , [39] , [54] , [55] , [57] , [58] , [62] , [64] , [65] , [76] , [79] , [82] , [89] [97] with 7,043 CAD patients and 10,409 controls, investigating the association between T786-C polymorphism and CAD were included in the pooled analysis. ( Tables 1 and 2 ) Moderate heterogeneity was seen across all genetic models ( I 2 range = 35–69%, P Q range = 0.03 to <0.00001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, meta-analysis provided by Kong XZ et al (2017) [30] is reported that 786СС polymorphism in eNOs gene corresponded well with increased risk of primary MI. Therefore, negative impact of the 786СС polymorphism in eNOs gene on a risk of death after MI was determined in manyfore populations [31][32][33][34] . However, previous clinical studies were tackled SNP in eNOs gene with endogenous NO production and vascular endothelial growth factor (VEGF), which is reported as key regulator of angiogenesis, coagulation and tissue reparation [35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…Because altered NO bioavailability in patients with 786CC polymorphism in eNOs gene can cause endothelial cell dysfunction, restenosis and early thrombosis of the stent 33,34 , we received a clinical confirmation regarding the independent negative impact of 786CC polymorphism in eNOs gene on MACE and hospital admission after STEMI over 6 months after completed reperfusion. Additionally, this finding can be important for acute STEMI patients with angiographically normal large coronary arteries, because there was evidence that 786CC polymorphism was associated with acute myocardial infarction, especially without severe coronary organic stenosis [35][36][37] . However, a risk of STEMI-related complications can sufficiently increase in individuals with 786CC polymorphism 38,39 .…”
Section: Discussionmentioning
confidence: 99%